CORRELATION STUDIES ON WEEDS AND TUBER YIELD IN POTATO - Panghal, V. S.; Nehra, B. K.; Khurana, S. C.; Singh, Narendra (Potato Journal, 2013)
Two experiments on chemical weed control in potato cultivar Kufri Badshah were conducted during autumn season of 2001-2002 and 2002-2003 at Hisar. Total tuber yield was related to number and dry weight of weeds recorded at 30, 60, and 90 days after planting (DAP), number and yield of A (>125g), B (>75-125g), C (>25-75g) and D (